The Moderating Role of Firm Size on ESG Disclosure in Stock Prices of Companies Listed on the Sri Kehati Index - Nadia Pentamitta Pandji; Zaky Machmuddah; Retno Indah Hernawati; Nila Tristiarini; Imang Dapit Pamungkas; Ngurah Pandji Mertha Agung Durya (Journal Management & Economics Review (JUMPER), 2026)
Investors are now considering environmentally friendly investments, focusing on ESG and sustainable investments. Public attention has forced companies to be transparent in reporting operational activities that have environmental, social, and governance impacts. This study aims to determine the relationship between environmental disclosure, social disclosure, and governance disclosure and stock prices. Furthermore, this study aims to determine the moderating role of company size in influencing environmental disclosure, social disclosure, and governance disclosure on stock prices. The population in this study was companies listed on the IDX Sri Kehati ESG Sector Leaders index on the Indonesia Stock Exchange (IDX). The sampling method used purposive sampling, with the criteria being companies listed on the IDX Sri Kehati ESG Sector Leaders index that were included in one or two indexing periods each year (June and December) for the two years 2022-2023. The results of the study indicate that environmental disclosure and social disclosure are not proven to affect stock prices, while governance disclosure is proven to affect stock prices. Other findings indicate that company size does not moderate the moderating role of environmental disclosure, social disclosure, and governance disclosure on stock prices. This indicates that even though companies manage their operations in an environmentally friendly manner and maintain good relationships with stakeholders, this doesn't yet signal a strong investment decision. Furthermore, a company's size doesn't guarantee that it is disciplined in maintaining environmental and social integrity, or that it is managing its business effectively, which can influence investor behavior.